Pulsed Cathodoluminescence of Irradiated LIF-O and LIF(U)-O Crystals; Optics and Spectroscopy; Vol. 105, № 4 - Lisitsyna L. A.; Oleshko V. I.; Putintseva S. N.; Lisitsyn V. M. Viktor Mikhailovich (2008, 2008)
В фонде НТБ ТПУ отсутствует